2016
DOI: 10.1093/abbs/gmv083
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted roles for thymine DNA glycosylase in embryonic development and human carcinogenesis

Abstract: Thymine DNA glycosylase (TDG) is a multifunctional protein that plays important roles in DNA repair, DNA demethylation, and transcriptional regulation. These diverse functions make TDG a unique enzyme in embryonic development and carcinogenesis. This review discusses the molecular function of TDG in human cancers and the previously unrecognized value of TDG as a potential target for drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…TDG encodes thymine DNA glycosylase, which participates in active DNA demethylation in the mammalian genome 35,36 . Therefore, decreased TDG levels may induce the accumulation of 5-hydroxymethylcytosine, 5-carboxylcytosine, and 5-formylcytosine 35,36 , which may lead to genomic instability and the occurrence of malignancy 41 . For instance, previous studies have reported that low levels of TDG expression are associated with poor prognosis in breast cancer (HR = 2.178, 95% confidence interval: 1.140-4.163, p = 0.018) 42 .…”
Section: Discussionmentioning
confidence: 99%
“…TDG encodes thymine DNA glycosylase, which participates in active DNA demethylation in the mammalian genome 35,36 . Therefore, decreased TDG levels may induce the accumulation of 5-hydroxymethylcytosine, 5-carboxylcytosine, and 5-formylcytosine 35,36 , which may lead to genomic instability and the occurrence of malignancy 41 . For instance, previous studies have reported that low levels of TDG expression are associated with poor prognosis in breast cancer (HR = 2.178, 95% confidence interval: 1.140-4.163, p = 0.018) 42 .…”
Section: Discussionmentioning
confidence: 99%
“…All these observations hint to a functional interplay between DNA methylation and demethylation processes to provide locus-specific epigenetic plasticity that allows post-developmental somatic cells to regulate transcriptional activity in response to environmental and systemic cues. Notably, TDG was shown to physically interact with variety of nuclear receptors, transcription factors and chromatin-regulating proteins as well as with DNMTs [8,126], indicating a central role in controlling DNA methylation states at regulatory regions of poised or active genes. Consistently, targeting TDG as well as TET proteins to silent genes was shown to effect DNA methylation changes and reactivate transcription [127,128].…”
mentioning
confidence: 99%
“…The methylation and demethylation of genomic DNA are important aspects of epigenetics, and two processes keeping balance each other to maintain the stability of methylation profiles. The TDG gene plays an important role in DNA repair, DNA demethylation, and transcription regulation and influences embryonic development and tumorigenesis [14]. Under natural conditions and accelerated oocyte aging conditions, the dynamic changes in the DNA demethylation of mouse oocytes under aging conditions are associated with TET3 gene over-expression and TDG inhibition [15].…”
Section: Discussionmentioning
confidence: 99%